Elegansi Perpaduan Syariah dan Tasawwuf - Nur Yasin (FALASIFA : Jurnal Studi Keislaman, 2017)
The human life in the world is not a coincidence but has been carefully arranged by God. Thus the consequences of Allah include shari'at as a prosecutor of human life and power of light in the form of devices that clarify the heart. In running a life in the world, people will get lost without shari'ah and will be meaningless without tasawwuf. Neither shari'ah nor tasawwuf should be taken either. Both must be implemented together in synergy. Shari'ah is the work of mind and tasawwuf the work of heart (heart) .Akal and kalbu are not two contradictory things, but both are human media to strengthen shari'ah and tasawwuf in him in order to reach the essential life.Â Keyword: Syariâ€™at, Tasawwuf, Akal, Hati